A case report on dermatofibrosarcoma protuberans with extensive myoid differentiation in breast: A rare presentation at an unusual site - Sobah, Nasheeda; K Parameswaran, Kavitha (Indian Journal of Case Reports, 2026)
Dermatofibrosarcoma protuberance (DFSP) is a rare, locally aggressive, cutaneous soft-tissue sarcoma characterized by a high propensity for local recurrence but a low metastatic potential. Its occurrence in the breast is extremely uncommon and may mimic benign or malignant breast lesions clinically and radiologically, posing a diagnostic challenge. Here, we present a case of a 42-year-old female, who presented with a slow-enlarging, firm, and painless swelling in the upper outer quadrant of the right breast for 1 month. Clinical and radiological evaluation suggested a benign spindle cell lesion. Histopathological examination revealed a spindle cell neoplasm with a storiform pattern arising from the dermis and infiltrating the surrounding breast tissue. Immunohistochemistry showed strong CD34 and h-caldesmon positivity and negativity for S-100, desmin, cytokeratin, and signal transducer and activator of transcription 6, confirming the diagnosis of DFSP with extensive myoid differentiation.